2018
DOI: 10.1103/physrevapplied.9.054012
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Low Internal Reorganization Energies for Silicene Nanoclusters

Abstract: High-performance materials rely on small reorganization energies to facilitate both charge separation and charge transport. Here, we performed DFT calculations to predict small reorganization energies of rectangular silicene nanoclusters with hydrogen-passivated edges denoted by H-SiNC. We observe that across all geometries, H-SiNCs feature large electron

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…It was further found that the reorganization energies for electron and hole transfer were roughly linearly dependent upon the reciprocal of the number of Si atoms in the Si QDs with slopes of 1.32 × 10 4 meV and 1.21 × 10 4 meV, respectively, as shown in Figure 6. This is consistent with the previously reported relationship for reorganization energy in CdSe dots and Si QDs 39,42,43 . These quantitative relationships make it possible to predict the charge transfer reorganization energies of Si QDs whose diameters has been experimentally confirmed.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…It was further found that the reorganization energies for electron and hole transfer were roughly linearly dependent upon the reciprocal of the number of Si atoms in the Si QDs with slopes of 1.32 × 10 4 meV and 1.21 × 10 4 meV, respectively, as shown in Figure 6. This is consistent with the previously reported relationship for reorganization energy in CdSe dots and Si QDs 39,42,43 . These quantitative relationships make it possible to predict the charge transfer reorganization energies of Si QDs whose diameters has been experimentally confirmed.…”
Section: Resultssupporting
confidence: 91%
“…This is consistent with the previously reported relationship for reorganization energy in CdSe dots and Si QDs. 39,42,43 These quantitative relationships make it possible to predict the charge transfer reorganization energies of Si QDs whose diameters has been experimentally confirmed. Our calculated electron and hole transfer reorganization energies of Si QD with a diameter of 1.03 nm (Si 35 H 36 ) were compared to those calculated for Si QD with the same diameter (Si 35 H 36 ) using the ab initio calculation reported previously.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations